Contemplating God with the great tradition : recovering trinitarian classical theism - Carter, Craig A., 1956-; Trueman, Carl R. (Grand Rapids, Michigan : : Baker Academic, a division of Baker Publishing Group, 2021)
"A leading Christian theologian presents the biblical and theological foundations of trinitarian classical theism"--
Foreword / by Carl R. Trueman -- Introduction: How my mind has changed -- Classical orthodoxy and the rise of relational theism -- What is trinitarian classical theism? -- Interpreting Isaiah 40-48 theologically -- God as the transcendent Creator (Isa. 40) -- God as the sovereign Lord of history (Isa. 41-48) -- God as the one who alone is to be worshiped (Isa. 41-48) -- The biblical character of pro-Nicene theology -- Creatio ex nihilo and the rejection of mythology -- Do we worship the God of the Bible? -- Epilogue: Why the church does not change its mind.
Includes bibliographical references (pages 309-319) and indexes.
Keywords: Trinity -- Biblical teaching; Trinity -- History of doctrines; Theism